2006
DOI: 10.1007/s10681-006-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

Progenies of allotriploids of Oriental × Asiatic lilies (Lilium) examined by GISH analysis

Abstract: With the aim of utilizing allotriploid (2n = 3x = 36) lily hybrids (Lilium) in introgression breeding, different types of crosses were made. First, using diploid Asiatic lilies (2n = 2x = 24), reciprocal crosses (3x − 2x and 2x − 3x) were made with allotriploid hybrids (AOA) obtained by backcrosses of F 1 Oriental × Asiatic hybrids (OA) to Asiatic cultivars (A). Secondly, the AOA allotriploids were crossed with allotetraploid (OAOA, 2n = 4x = 48), in 3x − 4x combination. Finally, the AOA allotriploids where cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 25 publications
5
14
0
1
Order By: Relevance
“…Most successful triploid 9 diploid/tetraploid crosses in Lilium could be explained by the new hypothesis Our 3x 9 2x and 3x 9 4x crosses were successful, as with previous reports in Lilium (Lim et al 2003;Barba-Gonzalez et al 2006;Khan et al 2009;Xie et al 2010). The success of these crosses can be well explained by the hypothesis that five same genomes of endosperm are essential for endosperm development in Lilium.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most successful triploid 9 diploid/tetraploid crosses in Lilium could be explained by the new hypothesis Our 3x 9 2x and 3x 9 4x crosses were successful, as with previous reports in Lilium (Lim et al 2003;Barba-Gonzalez et al 2006;Khan et al 2009;Xie et al 2010). The success of these crosses can be well explained by the hypothesis that five same genomes of endosperm are essential for endosperm development in Lilium.…”
Section: Discussionsupporting
confidence: 88%
“…Allotetraploids, such as LALA, OAOA, OTOT, have been produced by chromosome doubling on F1-distant hybrids with Cochicine or Oryzalin, and allotriploids, e.g., LAA, AOA, LOO and OTO, produced by diploid 9 tetraploid crosses or 2n gametes of F1 hybrids (Karlov et al 1999;Lim et al 2000Lim et al , 2001BarbaGonzalez et al 2004BarbaGonzalez et al , 2005aZhou et al 2008). Some progenies of a few interploid crosses '2x 9 3x', '3x 9 2x' and '3x 9 4x' have also been obtained in LA and OA lilies (Lim et al 2003; Barba-Gonzalez et al 2006;Zhou 2007;Khan et al 2009). In these studies, progenies of 3x 9 2x and 3x 9 4x crosses were mainly analyzed with GISH for their genome composition, intergenomic recombination or introgression between different lily genomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study it was found that in the progenies of 3x ¡ 2x crosses of LongiXorum £ Asiatic and 3x ¡ 2x and reciprocal crosses of Oriental £ Asiatic hybrids lilies, predominantly near diploid (i.e., aneuploid) or diploid progenies occurred indicating that triploid BC1 plants produced both balanced n as well as near haploid (e.g., n + 1 or n + 2 etc.) gametes Barba-Gonzalez et al 2006a). Similarly, present investigation shows that most of the BC2 progenies obtained after 2x ¡ 3x and in reciprocal crosses produced mostly diploid progenies.…”
Section: Discussionmentioning
confidence: 99%
“…This method was successfully applied in plants [Schwarzacher et al, 1989;Snowdon et al, 1997;Shibata and Hizume, 2002;Barba-Gonzalez et al, 2006] and fishes [Zhu and Gui, 2007;Valente et al, 2009]. In amphibians, Bi and Bogart [2006] performed GISH in unisexual salamanders of the genus Ambystoma (Amphibia, Caudata).…”
mentioning
confidence: 99%